ANALISIS SIMBOL DALAM CERITA RAKYAT DAYAK KANAYATN DIALEK BAJARE - Sinto, Sinto; Priyadi, Antonius Totok; Seli, Sesilia (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis research mean to know about reflected symbol that show relation between man to God, man to other man, and man to nature, then implemented in literary learning.This research used descriptive method and qualitative form with semiotic study by Charles Sander Peirce. Data source is text of folklore DayakKanayant dialect Bajare community, Setanduk village Capkala district Bengkayang regency. Data in this research is symbol that connect man to God, man to man, and man to nature. Data tools the researcher. Steps to collect the data is recording, transcription, translation, identification, and classification. The conclusion that is (1) symbol of relation man to God were buuhmalindo, asung, alu, bade, aikkasanggan, babont, manoksabungan, asukitamp, tumpi’ poe’, kapursirih, bontokng, barassasah, aikkasanggan, anger binyak, pa tekng-tekng, tapungktawar, kobetbasa’, kobetkarikng, penekngunyitmatabaras, lagor, tapayant, burukngketo, kaikngkuning, kaikngmerah, banang, (2) symbol of relation man to man were asung, alu, babont, manoksabungan, asukitamp, kapursirih, banang, burukngketo, (3) symbol of relation man to nature were hutan, babont, manok, asuk, burukngketo, kayuara, parahu, aikkasanggan. Keyword: Analysist, Bajare Dialect, DayakKanayant, Folklore, Symbol.